The SOSIALISASI DAN PRAKTIK PENGELOLAAN SAMPAH DI DESA SIPAK, KECAMATAN JASINGA, KABUPATEN BOGOR - Rachman, Nur Hadiyazid; Wijiharjono, Nuryadi; Yanto, Yanto (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2020)
The Central Bureau of Statistics reports that there is currently more waste in Indonesia for four reasons: (1) Indonesia now has a population of 261.89 million, up from 206.26 million in 2000; (2) Economic growth is accelerating, with the industrial sector contributing 2,739.4 trillion to GDP in 2014; (4) The development of people's consumption habits. This increased from only 2,739.4 trillion in 2000. This condition causes an increase in waste in terms of quantity, type, and quality. Waste problems also occur in Sipak Village. The lack of facilities and equipment to handle waste in Sipak Village, as well as the lack of community understanding of environmental management and sanitation, especially related to waste, are some of the causes of the accumulation of waste. Solutions that we can provide to our partners in this service activity include inviting the community to clean up the surrounding environment and providing waste management advice, establishing a waste bank, and processing waste into products that have selling value such as handicrafts, bricks, paraffin, and fuel (BBM).